Red Wine Classification Using SVM and RBF Kernel - Hutabarat, Kevin Silvanus; Kumalasanti, M.T., Rosalia Arum (Universitas Sanata Dharma, 2024)
Today’s cultural diversity has influenced lifestyle, especially at the time of certain events. Food and drink are important in the event. Quality food is a key ingredient in a person’s eating. Red wine is one of the most popular beverages in the West because of its cold climate but today Red wine has become a popular drink not only among Western countries. The love of red wine should also be balanced with his knowledge of the quality of the beverage because it has various variations. The duration of fermentation and the materials used will give different quality products. Nowadays technology is present to provide solutions to these problems by using the SVM algorithm on Machine Learning. The approach is carried out by performing several experiments to obtain optimal evaluation results. The study has achieved accuracy of 90.93%, precision of 72.5% and recall of 61.70%.Keywords: SVM, machine learning, accuracy, precision, recall